THU0060 Clinical Phenotypes of Systemic Sclerosis Impact Telomere and Telosome Function in Distinct Patterns. (23rd January 2014) - Broen, J.; McGlynn, L.; Geurts-van Bon, L.; Lafyatis, R.; Radstake, T.; Shiels, P.
Abstract : Background: Systemic sclerosis is a immune mediated inflammatory disease culminating in vasculopathy and extensive fibrosis of the skin and internal organs. Telomere shortening has previously been described in small cohorts of SSc patients. Objectives: To scrutinize previous findings in large cohort, investigate telomere shortening in multiple immune celltypes and scrutinize underlying aberrances in telosome gene expression. Methods: We measured telomere length by qPCR in a cohort of 185 SSc patients and 100 healthy controls. Next we investigated plasmacytoid dendritic cells, T cells, B cells, monocytes and myeloid dendritic cells from 25 SSc patients for cell specific telomere attrition. Finally we investigated whether there were differences in expression of 31 genes involved in telomere pathways. Results: A significant age related telomere attrition was observed in healthy controls and lcSSc patients (Both p< 0.001), but not in dcSSc patients. We observed significant shorter telomeres in B cells and myeloid dendritic cells of both lcSSc and dcSSc patients (B-Cells p=0.014, p=0.002 & myDCs p=0.019, p=0.004 respectively). PDCs and T cells had shorter telomeres in dcSSc patients only ( p=0.001 and p=0.003 ). In addition, we observed in early SSc, that B cells exhibit a significant upregulation of the telosome genes SIRT6, RIF1 and WRN (after correction for multiple testing p=0.03, 0.006 and 0.048 respectively). In later disease there is a significant higher expression of HDAC9 in monocytes from dcSSc compared to lcSSc patients. Intriguingly, in PDCs of diffuse SSc patients, regardless whether it is early or progressed disease the expression of SIRT1 is significantly lower ( p=0.002 in all comparisons). Image/graph: Conclusions: Aberrances in telomere shortening and biology are a feature of SSc, reflecting a difference in clinical subsets at the cellular level. Disclosure of Interest: None Declared